Konseling Online Media WhatsApp Pada Sexual Harassment Remaja Wanita Di SMK PGRI 2 Taman - Novita Oktaviani; M Arif Budiman; Sesya Dias Mumpuni (JCOSE Jurnal Bimbingan dan Konseling, 2022)
Sexual attraction of the opposite sex raises cases of sexual harassment regardless of age. The aim of the study was to find out the calming effects both physically and psychologically for victims of eliminating and utilizing whatsapp media for counseling services via the internet. The approach is through a mixed method problem method, namely collecting quantitative and qualitative data, combining the two forms of data and using different designs. Data collection techniques used are observation, questionnaires, interviews and audio-visual. The technique of presenting data analysis used by researchers is constructing and triangulating. The results of the questionnaire data found that students included in the score range 43-51 and 34-50 included in the total score category were 1 and 2 students. This study shows that one of the class XII AKL victims experienced physical sexual harassment by touching a woman's sensitive parts by an unknown person. Victims experience psychosocial impacts, feeling afraid, not confident or embarrassed to meet other people. The conclusion of the research is that the cause of sexual harassment is due to a quiet surrounding environment and lonely victims. The impact of victims experiencing psychosocial impacts and online counseling makes victims feel comfortable telling their problems. The advice given by counselors for women is always to be careful with the circumstances around them, maintain a polite appearance and not easily associate with the opposite sex which can trigger sexual attraction.